2017
DOI: 10.1007/s10729-017-9426-2
|View full text |Cite
|
Sign up to set email alerts
|

Reducing COPD readmissions through predictive modeling and incentive-based interventions

Abstract: This paper introduces a case study at a community hospital to develop a predictive model to quantify readmission risks for patients with chronic obstructive pulmonary disease (COPD), and use it to support decision making for appropriate incentive-based interventions. Data collected from the community hospital's database are analyzed to identify risk factors and a logistic regression model is developed to predict the readmission risk within 30 days post-discharge of an individual COPD patient. By targeting on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For three prognostic models, the non-linear association of predictors with the predicted outcome was considered using polynomials (n=1), fractional polynomials (n=1) and Box-Tidwell transformation (n=1). One study did a decision analysis after developing a prognostic model 24…”
Section: Resultsmentioning
confidence: 99%
“…For three prognostic models, the non-linear association of predictors with the predicted outcome was considered using polynomials (n=1), fractional polynomials (n=1) and Box-Tidwell transformation (n=1). One study did a decision analysis after developing a prognostic model 24…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in 30 different countries, with three in multiple countries [14,28,29]. The majority of studies were conducted in the USA (n=15) [17,[29][30][31][32][33][34][35][36][37][38][39][40][41][42], Spain (n=13) [13,28,29,[43][44][45][46][47][48][49][50][51][52] and Canada (n=9) [16,[53][54][55][56][57][58][59] [14,28,35,38,46,49,[60][61][62] and three (5.4%) reported only patient-related outcomes of readmission [63][64]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…After comprehensive assessment, study quality was identified as being good for most studies (n=50), with seven studies rating as fair [27,30,42,47,51,65,67] (Supplement D). The main area of weakness was lack of clarity in the definition and representativeness of readmitted patients.…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Predictive models use techniques such as logistic regression, survival analysis, and machine learning. Some articles focus on specific health conditions, such as Zhong et al (2019) [27] who developed a logistic regression model to predict readmission risks for high-risk COPD patients. Chen et al (2019) [28] introduced readmission risk models with the incorporation of latent heterogeneity to represent superior prediction performance, recognize risk factors to target the most at-risk individuals, and evaluate multiple hospitals with composite metrics.…”
Section: Predictive Approachesmentioning
confidence: 99%